2021
DOI: 10.21203/rs.3.rs-171264/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Radiographic Features and Prognosis of Early- and Late-onset Non-small Cell Lung Cancer Immune Checkpoint Inhibitor-related Pneumonitis

Abstract: Background: Immunotherapy is becoming a standard of care for non-small cell lung cancer (NSCLC). Checkpoint inhibitor-associated pneumonia (CIP) is a rare and potentially life-threatening event that can occur at any time during tumor immunotherapy. However, there may be differences in the radiological patterns and prognosis of CIP during different periods. This study aimed to investigate the radiographic features and prognosis of early- and late-onset immune-related pneumonitis. Methods: We retrospectively ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The onset of CIP was nonsignificantly earlier in the refractory group than in the nonrefractory group (16.57 vs. 7.43 wk, P =0.079). CIP with an onset ≤6 weeks and >6 weeks after ICI treatment was defined as early-onset and late-onset CIP, respectively 18,27. In addition, 92.9% of patients with early-onset CIP had grade 3 or higher CIP, with the mortality rate being as high as 50.0% 27.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The onset of CIP was nonsignificantly earlier in the refractory group than in the nonrefractory group (16.57 vs. 7.43 wk, P =0.079). CIP with an onset ≤6 weeks and >6 weeks after ICI treatment was defined as early-onset and late-onset CIP, respectively 18,27. In addition, 92.9% of patients with early-onset CIP had grade 3 or higher CIP, with the mortality rate being as high as 50.0% 27.…”
Section: Discussionmentioning
confidence: 99%
“…18,27 In addition, 92.9% of patients with early-onset CIP had grade 3 or higher CIP, with the mortality rate being as high as 50.0%. 27 Early-onset CIP has a much poorer prognosis than late-onset CIP. Our study demonstrated that the incidence of early-onset CIP was higher in the refractory group than in the nonrefractory group (50.0% vs. 18.2%, P = 0.021), which could explain the higher mortality rate in the refractory CIP group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic CIP is defined as persistent or worsening pneumonia after steroid reduction, and it is necessary to carry out immunosuppression for more than 12 weeks after ICI discontinuation 51 . Patients with early‐onset of CIP, within 6 weeks of ICI treatment, often have severe symptoms and poor prognosis, whereas patients with late‐onset of CIP, after 6 weeks of ICI treatment, often have few symptoms and better prognosis 52 …”
Section: Consensus 4: the Manifestations Of Cipmentioning
confidence: 99%
“…51 Patients with early-onset of CIP, within 6 weeks of ICI treatment, often have severe symptoms and poor prognosis, whereas patients with late-onset of CIP, after 6 weeks of ICI treatment, often have few symptoms and better prognosis. 52 The duration of CIP is variable from the beginning of ICI administration to withdrawal of the drug. Therefore, it is important to monitor CIP throughout the whole clinical process of ICI treatment.…”
Section: Clinical Manifestationsmentioning
confidence: 99%